Datasets on chemical composition and anaerobic digestion of organic fraction of municipal solid waste (OFMSW), digested sewage sludge (inoculum) and ashes from incineration or gasification - Sailer, Gregor; Eichermüller, Johanna; Poetsch, Jens; Paczkowski, Sebastian; Pelz, Stefan; Oechsner, Hans; Müller, Joachim (Data in brief, 2020)
This article contains data on the chemical composition and anaerobic digestion of different residue streams including OFMSW, digested sewage sludge, low-carbon (LC) ashes from incineration subdivided into LC coarse and LC fly ash as well as high-carbon (HC) ashes from gasification subdivided into HC reactor and HC fly ash. All materials were collected in accordance to standard procedures in southern Germany. The data presented in this article include (1) dry matter (2) organic dry matter (3) elemental analysis (4) trace elements and (5) cumulative biogas and CH4 yields. Researchers and waste management companies on lab-/pilot-/industrial-scale can rely on the presented data for classification and comparison of biogenic waste streams. For further discussion, please refer to the scientific article entitled “Optimizing anaerobic digestion of organic fraction of municipal solid waste (OFMSW) by using biomass ashes as additives” [1].